Экономическая восприимчивость производства к научно-техническим инновациям - Бажал Ю. Н. Юрий Николаевич; Александрова В. П. Валентина Петровна; Пасхавер А. И. Александр Иосифович; Тимощук Л. А.; Карноух Г. А.; Щедрина Т. И.; Казаченко С. В.; Гордань В. И.; Яковлев В. А.; Хмелевский Е. И.; Загорская Т. П.; Яблокова Н. Б. (Киев, Наук. думка, 1991)
Авт. указаны на обороте тит. л.